Shadow Children: Among the Barons - Book 4 - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 2003)
In a future world of false identities, government lies, and death threats, Luke feels drawn to the younger brother of the boy whose name Luke has taken.
Sequel to: Among the betrayed.
Keywords: Brothers -- Fiction; Fiction